Understanding the Impact of the Madden-Julian Oscillation and the North Atlantic Subtropical High on Atlantic Tropical Cyclone Variability - Campbell, Jacob (2022)
Tropical cyclone (TC) frequencies in the Atlantic Ocean have multiple influences of variability. Two important ones at subseasonal timescale are the Madden-Julian Oscillation (MJO) and North Atlantic Subtropical High (NASH). A detailed analysis into the combined effects of these together could be helpful in determining higher or lower TC frequencies in the Atlantic subregions – Caribbean, Gulf of Mexico, etc. – and the Atlantic as a whole. An established relationship could also be beneficial for forecasting TCs on a subseasonal timescale. This investigation identifies combinations of this corelationship utilizing contingency tables and chi-square independence analysis. It is shown there is a possible relationship between MJO and NASH where certain MJO phases modulate the NASH’s location and explain some TC frequency patterns. For the Gulf of Mexico, a combination of MJO phases 1-4 and a western NASH extension results in much higher TC counts than expected for a null hypothesis of no MJO/NASH effect. For the North American east coast, MJO phases 1 through 4 and a northeast NASH extension result in the most TCs. Vertical wind shear values related to MJO phases and observed NASH locations support these findings.